Hydration status, fluid intake, and electrolyte losses in youth soccer players - Williams, C. A.; Blackwell, J. (International Journal of Sports Physiology and Performance, 2012)
The purpose of the study was to determine the hydration status, fluid intake, and electrolyte losses of 21 male professional youth soccer players (age 17.1 ± 0.7 y) training in a cool environment. Pretraining and posttraining measurements of body mass, urine (freezing-point osmolality method), and sweat concentration (flame-emission spectroscopy) were collected. Fourteen players were found to be hypohydrated before training. The amount of fluid lost due to exercise equated to a 1.7% loss in body mass, which equated to a gross dehydration loss of 0.5%. Overall, the soccer players replaced 46% ± 88% of sweat loss during training, and only 4 remained hypohydrated after training. No significant correlations between sweat loss and sweat concentrations of Na+ (r = -.11, P = .67) or K+ (r = .14, P = .58) were found, but there was a significant correlation with Mg2+ (r = -.58, P < .009). This study found large variability in pretraining hydration status that the players were able to rehydrate during the training sessions. However, given the numbers starting training in a hypohydrated state, adequate hydration status before training should be considered by youth players, coaches, and sports-science support staff.